KARAKTERISTIK PENDERITA ASMA BRONKIAL RAWAT INAP DI RUMAH SAKIT UMUM DAERAH LANGSA TAHUN 2009-2012 - Desy Anriyani; Jemadi .; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Asthma Bronchial as a chronic respiratory disease. This disease which can happen in all of age. Based on data from RISKESDA 2007 asthma prevalence in Indonesia by 3,5% and the prevalence of diagnosis by health workers was 1,9%. To know characteristic of patients asthma bronchial hospitalizations in Langsa general hospitals 2009-2012. A descriptive study by using  case series design and data analysis by using Chi-Square and Mann-Whitney. Populations and samples in this study are all data of patient asthma bronchial hospitalizations in langsa general hospitals. Sampling with inclusion criteria, patient with asthma bronchial aged ≥14 years had complete  data recorded on the card status of patients treated in the first year. The highest proportion of patiens asthma  bronchial sufferers in the proportion of female (66,7%, Acehnese (68,6%), Muslem (100%), Occupation housewife (44,8%), Marital status is married (81,6%), Derived from Langsa (58,2%), Old of maintainability average  4,5 days (5 days), home with  outpatient care (88,1%), Instead of using their own expense (87,1%). The results obtained with Chi-Square test p>0,05 (p=0,059), there was no differences significant between age with sex. Mann-Whitney test p<0,05 ( p=0,000), meaning that there is a significant difference between the average maintainability length with the state when go home. Mann-Whitney test p>0,05 ( p=0,126), meaning that there is no significant difference between the average treatment time with the source charge. Chi-Square test p>0,05 (p=0,0815), there is no differences significant between the staet when go home with areas of origin. Keywords: Bronchial Asthma, characteristics, Langsa General Hospital